Rapid Switch from Intra-Aortic Balloon Pumping to Percutaneous Cardiopulmonary Support Using Perclose ProGlide - Kenichi Sakakura; Yusuke Adachi; Yousuke Taniguchi; Hiroshi Wada; Shin-ichi Momomura; Hideo Fujita (Case Reports in Cardiology)
We present a case of a patient who needed rapid switch from intra-aortic balloon pumping (IABP) to percutaneous cardiopulmonary support (PCPS)/venoarterial extracorporeal membrane oxygenation. It is difficult to switch from IABP to PCPS, because 0.035-inch guidewires cannot pass the IABP guidewire lumen (0.025-inch compatible), and the IABP sheath needs to be removed together with the IABP catheter. First, a 0.025-inch guidewire was inserted into the IABP wire lumen, and then the IABP catheter together with the 8 Fr IABP sheath was removed, leaving the 0.025-inch guidewire in place. We used the Perclose ProGlide for safe and rapid exchange of the 0.025-inch guidewire for a 0.035-inch guidewire. This allowed insertion of a PCPS cannula and the prompt initiation of PCPS.